1983
DOI: 10.1093/nar/11.14.4853
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of cDNA for pyruvate, Pi dikinase from maize leaves

Abstract: To obtain molecular probes for studies of gene regulation in photosynthetic tissues of maize, we have cloned DNA complementary to poly(A)+RNA extracted from green leaves by insertion into plasmid pBR322 and transformation of E. coli, strain RR1. Colonies were screened by sequential hybridization with 32P-labeled single stranded cDNA synthesized from pooled aliquots of poly(A)+RNA fractionated by sucrose density centrifugation. Among the clones bearing cDNA homologous to high molecular weight poly(A)+RNA, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
17
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…These results were further extended by Sims and Hague (8,21) who observed a photoinduced increase in translatable mRNA upon greening of maize leaf, and then by Harpster and Taylor (10) who quantitatively characterized the specific mRNA in maize leaf extracts. Also, Harpster and Taylor showed that during prolonged dark growth PEPC increased to nearly normal levels while its corresponding mRNA remained low.…”
mentioning
confidence: 57%
“…These results were further extended by Sims and Hague (8,21) who observed a photoinduced increase in translatable mRNA upon greening of maize leaf, and then by Harpster and Taylor (10) who quantitatively characterized the specific mRNA in maize leaf extracts. Also, Harpster and Taylor showed that during prolonged dark growth PEPC increased to nearly normal levels while its corresponding mRNA remained low.…”
mentioning
confidence: 57%
“…Either maize seed or wheat leaf PPDK is inactivated at a rate similar to that of maize leaf PPDK when placed in an inactivating mixture containing the regulatory protein which catalyzes light-mediated activation and inactivation ofPPDK activity (10). In both wheat and maize, the seed PPDK subunit is synthesized on cytoplasmic ribosomes as a 94 kD polypeptide (3), while in maize leaves (3,16) and in wheat leaves (3), it is synthesized as a 110 kD polypeptide which includes a 16 kD 'leader' that permits the polypeptide to be taken up by chloroplasts and processed to give the mature 94 kD polypeptide (4).…”
mentioning
confidence: 99%
“…The 1 10 kD polypeptide synthesized with maize leaf poly(A)RNA has been assumed to have a 16 kD 'leader' which facilitates entry into the chloroplasts, where it would be processed to give 94 kD WC GC SO.5 S1 S2. 5 Stages of differentiation PPDK polypeptide (12). This 110 kD polypeptide can be taken up and processed by isolated spinach chloroplasts (3).…”
mentioning
confidence: 99%
“…Regulation of the synthesis of PPDK in callus differs from regulation in leaftissue. In leaves, the synthesis of PPDK mRNA (12) and of PPDK polypeptides (14) are regulated quantitatively by light illumination whereas the level ofPPDK in callus seems to be independent of light. Moreover, although the concentration of PPDK in the callus tissue is much less than in leaves, the apparent Km (pyruvate) is only about one-third as large (Table I).…”
mentioning
confidence: 99%